The Use of ERP in Supporting Managerial Decision Making in Logistics Companies in Cikarang - Sono, Mohammad Gifari; Elisabeth, Christine Riani; Husaini, Husaini (Westscience Press, 2025)
This study investigates the role of Enterprise Resource Planning (ERP) systems in supporting managerial decision-making within logistics companies in Cikarang, Indonesia. As logistics operations become increasingly complex, the demand for integrated systems that provide real-time information and enhance decision quality has grown significantly. A quantitative research method was applied, involving 30 respondents selected from logistics companies actively using ERP. Data were collected using a 5-point Likert scale questionnaire and analyzed with SPSS version 25. The results of descriptive analysis show that respondents perceived ERP positively, with high mean values for both ERP usage (4.12) and managerial decision-making (4.25). Validity and reliability tests confirmed that all research indicators were valid and reliable. Regression analysis revealed that ERP usage has a positive and significant effect on managerial decision-making (β = 0.642, t = 5.734, p < 0.05), explaining 41.2% of the variance in decision-making effectiveness. These findings demonstrate that ERP contributes substantially to enhancing decision quality, timeliness, and strategic planning in logistics firms. The study concludes that while ERP is a vital enabler of decision-making, its success also depends on complementary factors such as managerial competence, organizational culture, and training.